Purā sampadā : a journal of Archaeology & Museums Deptt. of Rajasthan (Purāttava evaṃ Saṅgrahālaya Vibhāga, Rājasthāna, 2009)
Articles on antiquities, archaeology, monuments, history, culture, architecture, and arts of Rajasthan.